The seminal symphony: How to compose an ejaculate - Perry, J; Sirot, L; Wigby, S (2013)
Ejaculates are fundamental to fitness in sexually reproducing animals: males gain all their direct fitness via the ejaculate and females require ejaculates to reproduce. Both sperm and non-sperm components of the ejaculate (including parasperm, seminal proteins, water, and macromolecules) play vital roles in postcopulatory sexual selection and conflict, processes that can potentially drive rapid evolutionary change and reproductive isolation. Here, we assess the increasing evidence that considering ejaculate composition as a whole (and potential trade-offs among ejaculate components) has important consequences for predictions about male reproductive investment and female responses to ejaculates. We review current theory and empirical work, and detail how social and environmental effects on ejaculate composition have potentially far-reaching fitness consequences for both sexes. © 2013 Elsevier Ltd.